Incidence of spontaneous coronary artery dissection during pregnancy in Swedish women between 1997 to 2019, a retrospective observational cohort study based on national Swedish health-registers. (3rd October 2022) - Nebeski, D; Basic, C; Svanvik, T; Schaufelberger, M; Ostgard Thunstrom, E
Abstract: Background/Introduction: Spontaneous coronary artery dissection (SCAD) is an acute myocardial event. Previous studies suggest female predominance. It is an unusual underlying cause of myocardial infarction. However, it is thought to be the most common cause of myocardial infarction associated with pregnancy. Purpose: The aim of the study was to collect data on all women of reproductive age that had been diagnosed with SCAD in Sweden, including both pregnant and non-pregnant women, using the national Swedish health registers of the last two decades to describe the cohort and compare clinical characteristics. Methods: Retrospective data on individuals with a diagnosis of SCAD (ICD-I25.4) occurring before fifty years of age were collected from four Swedish registers; the national patient register, the national medical birth register, the national cause of death register and the LISA register. Women diagnosed with SCAD between the years 1997 and 2019 and <50 years of age at diagnosis were included. SCAD during pregnancy or within 14 weeks post-partum was considered pregnancy-associated. Results: A total of 75 women comprised the final cohort, seven of which met the criteria for pregnancy-associated SCAD. Nine percent of all women that had SCAD in Sweden before 50 years of age had it in association with pregnancy and in SCAD that occurred before 40 years of age, 28% arose in association with pregnancy. There were no clinically significant differences in height between women with pregnancy-associated SCAD and those with SCAD not associated with pregnancy. History of smoking, diabetes mellitus, hyperthyroidism, hypothyroidism and hyperlipidemia were not prominent in the cohort (9.3, 4, 1.3, 2.7 and 2.7% respectively). Seventeen percent of patients had had no pregnancies prior to first event of SCAD. Two patients (2.6%) were deceased due to ischemic heart disease, one had had SCAD associated with pregnancy. Conclusion: Spontaneous coronary artery dissections are uncommon. However, when they do occur in women under forty years of age more than one in four (28%) is associated with pregnancy. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Swedish heart lung foundation.